2006
DOI: 10.1007/s00264-006-0284-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the utility of the Ponseti method of correction of clubfoot deformity in a developing nation

Abstract: Clubfoot is the commonest congenital deformity in babies. More than 100,000 babies are born worldwide each year with congenital clubfoot. Around 80% of the cases occur in developing nations. We treated 154 feet [mean Pirani score (total) 5.57] in 96 children (78 males, 18 females) by the Ponseti method from January 2003 to December 2005. A prospective follow-up for a mean duration of 19.5 months (range 6-32 months) was undertaken. After six months of treatment the Pirani score was reduced to zero for all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 22 publications
10
63
0
1
Order By: Relevance
“…With the perception that the treatment of idiopathic clubfoot by extensive soft tissue release is often complicated by stiffness, recurrence, and the need for additional procedures, many treatment centers have adopted the minimally invasive Ponseti method, which has achieved excellent results in both economically developed [1-4, 6-8, 10, 11, 13, 14, 16, 18, 19, 21-26] and underdeveloped regions [9,12,17,28]. Although the majority of patients in these studies have been treated in infancy, recent evidence suggests the method may be appropriate for patients of walking age [9,17,28], and the upper age limit remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…With the perception that the treatment of idiopathic clubfoot by extensive soft tissue release is often complicated by stiffness, recurrence, and the need for additional procedures, many treatment centers have adopted the minimally invasive Ponseti method, which has achieved excellent results in both economically developed [1-4, 6-8, 10, 11, 13, 14, 16, 18, 19, 21-26] and underdeveloped regions [9,12,17,28]. Although the majority of patients in these studies have been treated in infancy, recent evidence suggests the method may be appropriate for patients of walking age [9,17,28], and the upper age limit remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…However, many complications were encountered with operative treatment such as forefoot adduction (range, 17%-81.1%), cavus (range, 5.9%-45.5%), overcorrection (range, 3.8%-22.2%), hindfoot equinus or varus (range, 7.2%-41.5%), and avascular necrosis of the talus (range, 3.2%-14.3%) [2,25,33]. Consequently, some centers around the world [1,8,12,19,21,22] revived the Ponseti method with deformity correction being maintained short-and long-term. The importance of using postcasting abduction splints to maintain correction was stressed by Ponseti [28] and others [1,8,12,19,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 24 (80%) indicated that they did need more training and made comments relating to which aspects of training was needed, including: follow up [1], more Ponseti, especially practical [4], anterior tibial tendon transfer [1], casting and manipulation [10], tenotomy [10], FAB [1], surgery [1], older cases [1], and updates [1]. Figure 4 shows the responses of the trainees to the parent's understanding and acceptance of the Ponseti method.…”
Section: Survey Resultsmentioning
confidence: 99%